Be quiet, Mike! - Patricelli, Leslie (Somerville, Mass. : Candlewick Press, 2011)
Monkey Mike is always making noise, tapping pencils and clanging trash cans, but when he sees a drum set in a music store, he is able to really put his talents to work.
Kirkus Review
Publisher's Weekly
School Library Journal
Kirkus Review, July 2011
Publisher's Weekly, June 2011
School Library Journal, August 2011
Keywords: Drum -- Juvenile fiction; Monkeys -- Juvenile fiction; Musicians -- Juvenile fiction; Noise -- Juvenile fiction; Drum -- Fiction; Monkeys -- Fiction; Musicians -- Fiction; Noise -- Fiction; Stories in rhyme; Drums -- Fiction; Monkeys -- Fiction; Musicians -- Fiction; Noise -- Fiction; Stories in rhyme; Picture books for children